ETHNOMATHEMATICS EXPLORATION OF TWO-DIMENSIONAL PLANE FIGURES IN TUATUNU GRAND MASJID: INTEGRATING GEOMETRY INTO MATHEMATICS EDUCATION - Fahlevi, Mahfudz Reza; Lubis, Riyani Fitri (Universitas Tanjungpura, 2025)
This research project was conducted to investigate the mathematical aspects, specifically focusing on two-dimensional geometry concepts found in the architectural design of the Tuatunu Grand Masjid, which aimed to integrate these research findings into the mathematics education curriculum. Utilizing a descriptive qualitative methodology from an ethnographic standpoint, information was collected through interviews with two takmir (masjid administrators), as well as through direct observation and documentation. The primary data collection method was direct interaction with participants, which could benefit from further explanation to clarify the specific types of interactions conducted. The analysis process followed Spradley